THE CONCEPT OF ENCULTURATION IN CROSS-CULTURAL COUNSELING - Maftuhah, Siti; Aris, Sarmen; Elfira, Ninil (Jurnal Masyarakat Religius dan Berwawasan, 2024)
Enculturation is a concept needed in the era of globalization and modernization in maintaining and maintaining existing cultural diversity. Each individual has different cultural elements that are interrelated with each other. Thus, each individual cannot be separated from cultural elements, as well as in the process of cross-cultural counseling. So through the literary riview method, the concept of enculturation is studied and examined more deeply in cross-cultural counseling, resulting in a statement that this concept is a necessity that is needed in the cross-cultural counseling process, because cultural elements have unity and attachment to one another, both in terms of knowledge, arts, crafts, morals, laws, and customs. So that it can help the counseling service process become more effective.